2015
DOI: 10.1177/1091581815602252
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Dietary Supplements from Annonaceae Species

Abstract: Dietary supplements containing plant materials of Annonaceae species (Annona muricata L., A. squamosa L., A. mucosa JACQ., A. squamosa × cherimola Mabb.) were extracted by hot, pressurized ethyl acetate and analyzed for their effect in vitro on Lund human mesencephalic neurons. Cell viability was measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and cell death was determined by lactate dehydrogenase levels. Three supplements strongly decreased the cell viability at extract con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The AAGs contents varied greatly between the samples, from 14 to 226 μmol per 100 g of fresh pulp (sample C – Mauritius Island and sample G – New Caledonia, respectively, yielding 0.14 to 1.3 mmoles per fruit; Table ). These results are in accordance with the order of magnitude proposed in previous estimations for annonacin (Champy et al, ; Hölleraghe et al , ). Interestingly, fruits obtained from the same location at a one year interval had similar content in AAGs of sub‐types 1a and 1b (samples A and B), while others from close areas and dates of harvest showed a 1.7‐fold difference (samples C and D).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The AAGs contents varied greatly between the samples, from 14 to 226 μmol per 100 g of fresh pulp (sample C – Mauritius Island and sample G – New Caledonia, respectively, yielding 0.14 to 1.3 mmoles per fruit; Table ). These results are in accordance with the order of magnitude proposed in previous estimations for annonacin (Champy et al, ; Hölleraghe et al , ). Interestingly, fruits obtained from the same location at a one year interval had similar content in AAGs of sub‐types 1a and 1b (samples A and B), while others from close areas and dates of harvest showed a 1.7‐fold difference (samples C and D).…”
Section: Resultssupporting
confidence: 93%
“…The NMR profiles of the extracts evidenced a steady ratio between AAGs of sub‐types 1b (~72%) and 1a (~28%), except for sample C (~90%/10%). It is known that annonacin ( 1 ) (sub‐type 1b) is the main AAG in Annona muricata fruits (Champy et al, ; Höllerhage et al, ), but investigation of a soursop nectar by HPLC‐ESI‐LTQ‐Orbitrap® had previously evidenced the presence of sub‐type 1a AAGs in important proportions (Le Ven et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,18,[25][26][27][28][29][30][31] Among the studies investigating hepatic effects, eight studies demonstrated a hepatoprotective effect of A. muricata leaf extracts [16,18,[25][26][27][28]30,31] while one study demonstrated a hepatotoxic effect with no substantial differences in the dose, formulation or route of administration. [29] Three in-vitro and one animal study identified neurotoxic effects (n = 4), [32][33][34][35] with the animal study using annonacin at a dose of 3.8-7.6 mg/kg per day when administrated intravenously to rats for 28 days. One animal study utilised ethanolic leaf extract at a dose of 25-100 mg/kg demonstrated sedative, anxiolytic and anticonvulsant-like effect.…”
Section: Chemopreventive Potentialmentioning
confidence: 99%
“…Sugar apple ( Annona squamosa L.) is an important member of the Annonaceae family, which consists of ~166 genera and more than 2000 species (Höllerhage et al, 2015). As a commercially important fruit tree, sugar apple orchards are wide spread and well adapted to the edaphoclimatic conditions of tropical and subtropical zones.…”
Section: Introductionmentioning
confidence: 99%